Determining Factors of Length of Stay of Indian Domestic Tourists - Tapas Kumar Chatterjee; Bikramjit Rishi (ASEAN Journal on Hospitality and Tourism, 2020)
There is a trend of shortening lengths of stay (LOSs) in tourism, coupled with more frequent trips. Since tourism revenue derives from the duration of stay of tourists at destinations, tourism marketers are interested in attracting those tourists who stay for longer, and thus more profitable durations. Indian domestic tourism is a huge market but it has been insufficiently researched. As a result,  destination marketing organizations (DMOs) are constrained to depend more on hunches in their efforts to attract tourists. This study attempts to identify the determining factors of length of stay of Indian domestic tourists with empirical evidence adopting multiple regression and the MARS (multivariate adaptive regression splines) model. The findings fill an essential gap in the tourism literature, as pertains to lengths of stay at Indian destinations. They also help destination marketing organizations better understand the nuances of tourist behavior, so they can craft appropriate marketing strategies that attract those tourists who tend to stay for longer durations.